التفسير اللغوي للنص القرآني - جدلية الاستثمار والاستغلال - حذيق (جامعة الوادي university of eloued, 2023)
هذا المقال بعنوان: التَّفسير اللُّغويُّ للنَّصِّ القُرآنيِّ - جدليَّة الاِستثمار والاِستغلال -. وهو دراسةٌ في إشكاليَّة توظيف التفسير اللغوي لنص القرآن الكريم، في مُدونات التفسير التراثية، وكشفٌ لأنماط تعامل المفسرين مع هذه القضية؛ إذ أن المتأمل في هذه المسألة، يتَّضح له توجُّهان بارزان في توظيفها: توجُّهٌ ينطلق من المحتملات اللغوية في النص القرآني ليصل إلى بيان معناه؛ فهي نقطة البداية عنده. وتوجُّهٌ يعكسُ الأمر؛ فينطلق من المُقرَّرات العقديَّة، ويوظِّف إمكانات اللغة وسَعتها في تأويل النص القرآني لنُصرة ذلك المقرَّر العقديِّ، فهي نقطة النهاية عنده. ولمعالجة هذا الإشكال؛ بنيتُ أركان المداخلة على مقدِّمةٍ، ومقصدين وخاتمة. أمَّا المُقدِّمةُ؛ فقد تم فيها تحرير الإشكال الَّذي يطرحُه الموضوع، وبيان بعض القضايا التي ينبني عليها البحث؛ من قبيل: أهمية اللغة العربية للمفسر، وضوابط الاعتماد على اللغة في التفسير. وأمَّا المقصد الأوَّلُ؛ أثر التأويل اللغويِّ في اختلاف المفسرين؛ فيمثِّل الجانب الإيجابي في استثمار التفسير اللغوي، وهو ما يُطلق عليه بعض أهل الشَّأن: اختلاف التنوع، أي تكثير المعاني والدلالات للنص الواحد، دون تعارض أو مناقضة. وأمَّا المقصد الثَّاني؛ استغلال التأويل اللغويِّ للانحراف بالتفسير؛ فيمثل الجانب السلبيَّ من القضيَّة؛ إذ يُصبح التأويل اللغوي تابعًا لا متبوعًا، يُلوى عُنُقه ليُوافق مقصُودَ المؤوِّل. وقد توصلتُ في الخاتمة إلى نتائج أهمُّها: أن اللغة العربية على أهميتها لا تستقل بإدراك التفسير، بل الاعتمادُ عليها بمجردها يُعتبر من موارد الخطأ في التفسير. وأن أسلم طريق مُوصلٍ إلى نتائج علمية صحيحة في التفسير؛ هو الانطلاق من النص القرآني ذاته، لا من المُسَلَّمَات القبلية. This paper entitled "The Linguistic Interpretation of the Qur'anic Text-The Dialectic of Investment and Exploitation" dives into the issue of employing the linguistic interpretation of the text of the Holy Qur'an in the traditional interpretation records ; and tries to reveal the different patterns of interpreters dealing with this issue. Two prominent trends in the use of linguistic interpretation of the Qur'anic text become clear to the contemplator of this issue. An orientation that starts with the linguistic potentials in the Qur'anic text to reach a statement of its meaning. In this case, the linguistic interpretation is the starting point of this trend. And an attitude that reverses the equation by starting from the doctrinal decisions and employing the potentials of the language and its capacity to support those doctrinal decisions which are this trend's end point. To address this issue, this paper is designed in the form of an introduction , two chapters , and a conclusion. In the introduction, the studied problem is thoroughly presented and some of the cases on which the research is built are elucidated such as the importance of the Arabic language to the interpreter and the regulations that govern the dependency on Arabic in the process of interpreting . The first chapter –The Impact of Linguistic Interpretation on the Variation of Interpreters- provides an insight into the positive side of investing in the linguistic interpretation, which is what people in the field call: the difference of diversity, that is; the multiplication of meanings and connotations of the same text without conflict or contradiction. The second chapter –The Exploitation of Linguistic Interpretation in Deviating the Interpretation- introduces the negative side of the issue where the linguistic interpretation becomes subservient to the interpreters who twist it to match their intent. Lastly, the conclusion exhibits the most important results : 1. The Arabic language, despite its importance, is dependent on the comprehension of the interpretation ; rather, relying on language by itself is considered one of the sources of error in interpretation. 2. And the safest way to correct scientific results in interpretation is to start from the Qur'anic text itself, not from the axioms
مقال
Keywords: التفسير؛ اللغة العربية؛ الاستثمار؛ الاستغلال؛ الدلالات